Evaluation of the orientation distribution of fibers from reflection images of fibrous samples. Issue 1 (27th January 2014) - Takalo, Jouni; Timonen, Jussi; Sampo, Jouni; Marjanen, Kalle; Siltanen, Samuli; Lassas, Matti
<x content-type="archive" xml:space="preserve">Abstract</x> We consider illumination systems and mathematical algorithms for determination of the anisotropy and topographical features of an illuminated surface from its reflection images. As a particular example we study determination of the fiber orientation of paper surface. We also consider illumination systems with multiple light sources, and introduce optimization algorithms that exploit different spectral bands of these light sources. We show that a system of three light sources, e.g., a blue, green and red LED placed in a regular triangular form, efficiently prevents distortion of the above features. It is also easy to implement in applications, e.g., of the paper industry. We furthermore show that a pentagonal illumination system would be even better. However, in this case a five-colour photographic system and the corresponding light sources would be needed.